2019
DOI: 10.1111/1747-0080.12569
|View full text |Cite
|
Sign up to set email alerts
|

Australian team sports athletes prefer dietitians, the internet and nutritionists for sports nutrition information

Abstract: Aim To evaluate the information sources that are used and preferred by Australian athletes and to assess if preferences influence nutrition knowledge (NK). Methods Elite and non‐elite Australian team sport athletes, playing Australian football (AF), cricket, lawn bowls, soccer or hockey, were recruited via the sporting organisations' qualified sports dietitians or club presidents. Athletes completed one of two online, validated sports NK questionnaires. Frequency analysis on previous sources of advice, preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
35
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 34 publications
12
35
4
4
Order By: Relevance
“…Crino et al also describe that women favour online methods for advertising and recruitment for weight management trials . Athletes equally prefer the internet and dietitians as their nutrition information source . With this in mind, the findings by Probst and Peng that only a third of Australian dietitians use social media professionally demonstrate a disconnect between what consumers want and what professionals are providing .…”
Section: The Internet Social Media and Print Media For Accessing Heamentioning
confidence: 99%
See 2 more Smart Citations
“…Crino et al also describe that women favour online methods for advertising and recruitment for weight management trials . Athletes equally prefer the internet and dietitians as their nutrition information source . With this in mind, the findings by Probst and Peng that only a third of Australian dietitians use social media professionally demonstrate a disconnect between what consumers want and what professionals are providing .…”
Section: The Internet Social Media and Print Media For Accessing Heamentioning
confidence: 99%
“…13 Athletes equally prefer the internet and dietitians as their nutrition information source. 8 With this in mind, the findings by Probst and Peng that only a third of Australian dietitians use social media professionally demonstrate a disconnect between what consumers want and what professionals are providing. 9 The 2019 Decadal Plan for nutrition science in Australia identifies the opportunities that exist for nutrition professionals to harness the communication power of social media and the internet.…”
Section: The Internet Social Media and Print Media For Accessing Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted from Trakman et al (2019), 410 Australian elite and non-elite sports teams were surveyed about previous sources of nutrition advice and their preferred sources of nutrition information. The results of this study of this study showed that of the surveyed athletes, 44% reported previously being given nutrition advice from a dietitian yet the question did not specify whether the dietitian specialized in sports nutrition.…”
Section: Sports Nutrition Dietitians' Impactmentioning
confidence: 99%
“…The results of this study of this study showed that of the surveyed athletes, 44% reported previously being given nutrition advice from a dietitian yet the question did not specify whether the dietitian specialized in sports nutrition. Furthermore, 59% reported neither having access to a dietitian nor receiving nutrition information while 87% believed having access to a dietitian or nutritionist should be available (Trakman et al, 2019). Twenty percent, 19% and 16% of athletes chose "dietitian," "internet" and "nutritionist" as their preferred source of nutrition information (Trakman et al, 2019).…”
Section: Sports Nutrition Dietitians' Impactmentioning
confidence: 99%